Adult-onset Kawasaki disease: A great masquerader. Issue 3 (16th March 2021) - Datta, Amlan Kusum; Debnath, Partha; Chaudhuri, Jasodhara; Mukherjee, Adreesh
Abstract : Kawasaki disease is a necrotising small-to-medium vessel vasculitis affecting children between age groups of 6 months and 5 years. Following the first description in Japanese infants, it has been recognised as the single most common cause of non-infectious vasculitis in children worldwide. Presentation in adult age groups, although described, is rare. Herein, we report a case about a 19-year-old female Indian patient diagnosed with Kawasaki disease and managed with antiplatelets and intravenous immunoglobulin, without further sequalae. We aim to highlight the importance of recognising this entity in adult age groups in day-to-day clinical practice.